Countercyclical Labor Income Risk and Portfolio Choices over the Life Cycle - Catherine, Sylvain (Review of Financial Studies, 2022)
I estimate a life cycle model of portfolio choices that incorporates the relationship between market returns and the skewness of idiosyncratic income shocks. The cyclicality of skewness can explain (a) low stock market participation among young households, (b) why the equity share of participants slightly increases until retirement, and (c) why renters invest less in stocks than do homeowners. With a relative risk aversion of 6 and yearly participation cost of $250, the model matches the evolution of wealth, participation, and conditional equity shares over the life cycle. Nevertheless, cyclical skewness increases the equity premium by at most 0.5 percentage points. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.